HUBUNGAN ANTARA GANGGUAN PENDENGARAN DENGAN SERUMEN PADA LANSIA DI PUSKESMAS MEDAN JOHOR - Alamsyah Lukito (Jurnal Penelitian Kesmasy, 2019)
The human ear is a hearing organ that captures and changes sound in the form of mechanical energy into electrical energy efficiently and is passed on to the brain to be realized and understood. Serum that collects and forms masses will clog the ear canal, causing interference with the sound that results in hearing loss. The research that will be conducted is a study with a cross-sectional method with a sample of 52 people. The majority of respondents were men with a majority of elderly with an average age of 67 years. The results showed that respondents who had serumen were as much as 59.6% and those who had hearing loss were 63.5%. This shows that there is a relationship between hearing loss and the presence of serumen.